Synthesis of Analcime Crystals and Simultaneous Potassium Extraction from Natrolite Syenite - Jian Chen; Hongwen Ma; Changjiang Liu; Jiangyan Yuan (Advances in Materials Science and Engineering)
Analcime single crystals were successfully synthesized from natrolite syenite powder (K2O 10.89%) and 92.6% of potassium was extracted simultaneously by means of soda roasting followed by alkali-hydrothermal method. Effects of NaOH concentration, reaction temperature, and holding period on the analcime formation and potassium extraction were investigated systemically. The results indicated that NaOH concentration plays an important role in determining the chemical composition of zeolites and size distribution; by turning the NaOH concentrations, three different pure zeolites (i.e., the phillipsite-Na, the analcime, and the sodalite) were prepared. Besides, a higher temperature could accelerate the dissolution of K+ ions and enhance the crystallinity degree of zeolite. The reactions involved in the analcime synthesis can be summarized as follows: sodium aluminum silicate dissolution → precipitation and dissolution of metastable zeolite-P → analcime nucleation → analcime growth. The extraction ratio of K+ is associated with the types of synthesized zeolites, among which analcime is the most effective to promote potassium leaching out from zeolite lattice position. The optimal condition for analcime crystallization and K+ leaching is found to be as follows: 175°C for 4 h in 0.5 mol/L NaOH solution.